Hemostatic laboratory derangements in COVID-19 with a focus on platelet count. (17th August 2020) - Amgalan, Ariunzaya; Othman, Maha
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the coronavirus disease in 2019 (COVID-19) which rapidly evolved from an outbreak in Wuhan, China into a pandemic that has resulted in over millions of infections and over hundreds of thousands of mortalities worldwide. Various coagulopathies have been reported in association with COVID-19, including disseminated intravascular coagulation (DIC), sepsis-induced coagulopathy (SIC), local microthrombi, venous thromboembolism (VTE), arterial thrombotic complications, and thrombo-inflammation. There is a plethora of publications and conflicting data on hematological and hemostatic derangements in COVID-19 with some data suggesting the link to disease progress, severity and/or mortality. There is also growing evidence of potentially useful clinical biomarkers to predict COVID-19 progression and disease outcomes. Of those, a link between thrombocytopenia and COVID-19 severity or mortality was suggested. In this opinion report, we examine the published evidence of hematological and hemostatic laboratory derangements in COVID-19 and the interrelated SARS-CoV-2 induced inflammation, with a focussed discussion on platelet count alterations. We explore whether thrombocytopenia could be a potential disease biomarker and we provide recommendations for future studies in this regard.